2020
DOI: 10.22541/au.159414506.65558424
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abnormal thyroid test results in euthyroid state: An appraisal of the role of drugs

Abstract: Background: Thyroid function tests (TFTs) are one of the most frequently performed hormonal tests. Abnormal reports are commonly encountered even in the absence of thyroid dysfunction with medication use during testing being an important cause of this anomaly. Knowledge about the effects of different drugs on various components of TFTs will prevent unnecessary referrals, investigation and potentially dangerous therapeutic decisions. Objective: This narrative review aims to provide information to physicians reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Low T3 syndrome, also known as the euthyroid sick syndrome (ESS) could be responsible partly for high prevalence of thyroid dysfunction in COVID-19. This syndrome is known to occur in 60 to 70% of critically ill patients regardless of the cause ( 58 ) and in different studies in admitted patients due to COVID, ESS was presented in around 30% patients(up to 64%) and were related to severity, longer hospitalization and mortality ( 40 , 59 ). Similarly, studies have suggested a significant inverse correlation between the severity of illness and low serum total T3.…”
Section: Discussionmentioning
confidence: 99%
“…Low T3 syndrome, also known as the euthyroid sick syndrome (ESS) could be responsible partly for high prevalence of thyroid dysfunction in COVID-19. This syndrome is known to occur in 60 to 70% of critically ill patients regardless of the cause ( 58 ) and in different studies in admitted patients due to COVID, ESS was presented in around 30% patients(up to 64%) and were related to severity, longer hospitalization and mortality ( 40 , 59 ). Similarly, studies have suggested a significant inverse correlation between the severity of illness and low serum total T3.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the target tissue, tamoxifen can have different biological actions: predominantly anti‐oestrogenic effects in the breasts, yet oestrogenic effects in the uterus and the liver. 58 Tamoxifen causes a mild increase in TBG concentrations in the liver, 58 possibly as a result of an intrinsic, enhanced oestrogen‐agonistic effect. 36 , 38 , 59 Mirzaei et al speculated on tamoxifen bind to a protein with heavier glycoside than normal TBG, reducing TBG clearance and evoking TBG increase.…”
Section: Discussionmentioning
confidence: 99%